EVALUASI PROGRAM KAIZEN DI BENGKEL OTOMOTIF SMK NEGERI 1 MAGELANG - Johny Rianingsih; Tafakur Tafakur; Sabbihis Sayyidi; Albino Mauzino; Ghany Desti Laksita (Universitas Negeri Yogyakarta, 2026)
This study aims to evaluate the implementation of the Kaizen program in the automotive workshop of SMK Negeri 1 Magelang using the CIPP (Context, Input, Process, and Product) evaluation model. This evaluative study analyzes the appropriateness of the context, the adequacy of inputs, the implementation of processes, and the resulting products of the program. The research population consisted of 99 eleventh-grade students from the Light Vehicle Engineering (Automotive) program and 9 automotive teachers, with samples selected through purposive sampling based on their involvement in the program. Data collection was carried out using questionnaires, semi-structured interviews, and non-participant observation. Instrument validity was tested through expert judgement, and its reliability was calculated using the Cronbach's Alpha coefficient in SPSS. Data were analyzed quantitatively and qualitatively. The evaluation results show that the context aspect scored 81.42% (in the appropriate category), while the input (77.31%), process (77.25%), and product (75.87%) aspects were in the fairly appropriate category. Overall, the implementation of the Kaizen program is considered fairly appropriate. The study concludes by recommending the continuation of the program with improvements in the input, process, and product aspects to enhance its effectiveness and achieve more optimal outcomes.